2004
DOI: 10.1007/s00535-003-1286-5
|View full text |Cite
|
Sign up to set email alerts
|

Early decrease in serum IV-7S levels during IFN treatment predicts anti-fibrogenic effect in nonresponders with chronic hepatitis C

Abstract: An early decrease in IV-7S levels after IFN treatment is a useful indicator of anti-fibrogenic effects in nonresponders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
(57 reference statements)
1
3
1
Order By: Relevance
“…Although PPIs are the antisecretory drugs of choice for GERD, they are not considered good candidates for treatment of very short episodes because of the rather long lag time needed to increase intragastric pH [4 [13]. Indeed, our study showed that PPIs required longer time to increase gastric pH above 4 compared to ranitidine, and this finding is compatible with results reported by others [9][10][11][12][14][15][16]. However, our results are in contrast to studies showing that gastric pH failed to rise above 4 in the majority of subjects after PPI treatment during a 6-h period [9,13].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Although PPIs are the antisecretory drugs of choice for GERD, they are not considered good candidates for treatment of very short episodes because of the rather long lag time needed to increase intragastric pH [4 [13]. Indeed, our study showed that PPIs required longer time to increase gastric pH above 4 compared to ranitidine, and this finding is compatible with results reported by others [9][10][11][12][14][15][16]. However, our results are in contrast to studies showing that gastric pH failed to rise above 4 in the majority of subjects after PPI treatment during a 6-h period [9,13].…”
Section: Discussionsupporting
confidence: 95%
“…Gastric pH remained above 4 at the end of the study in all subjects with omeprazole and esomeprazole and in all except one with rabeprazole, while only four subjects with ranitidine sustained a pH [4. This finding was unexpected because previous studies have shown that during the early postadministration period, H 2 RAs had a greater longstanding effect on gastric pH compared to PPIs [9][10][11][12][14][15][16]. All studies were carried out in healthy, H. pylori (-) subjects; thus, we can speculate that differences either in doses and formulations of the drugs or in fasting status of the subjects could explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, we discovered PPI was more effective in bleeding prevention than H 2 RA for 8-week medication duration, not for 4-week medication duration. It might be by reason that PPI was not fast acting, compared with more rapid effects of H 2 RA in reaching the optimal gastric pH [12,19]. Some studies reported bleeding and ulcer healing were associated with lesion size and tumor location [20,21], but it was difficult to stratify patients by these factors in our meta-analysis.…”
Section: Discussionmentioning
confidence: 66%
“…Until now, a higher IFN dosage has been administered in Japan than in western countries. In Japan, the standard protocol of IFN‐α2b monotherapy for patients with CHC is 6–10 MU of IFN‐α every day for the first 2–4 weeks and then three times a week for the following 20–22 weeks 31–33 . Medical health insurance can cover medical expenses for up to 6 months of IFN‐α2b and ribavirin therapy, irrespective of a total dose of IFN‐α2b.…”
Section: Discussionmentioning
confidence: 99%